Grain aphid clones vary in frost resistance, but this trait is not influenced by facultative endosymbionts - Lukasik, P; Hancock, E; Ferrari, J; Godfray, C (2011)
1. Facultative endosymbiotic bacteria of insects are known to affect life-history traits of their hosts, and can provide important fitness benefits under certain environmental conditions. While several distinct endosymbiont-induced effects have been reported, there is no data on whether heritable facultative endosymbionts in any species affect their hosts' performance at low temperatures, something that could have a major effect on insect physiology and survival, and thus population structure and distribution. 2. The original facultative endosymbionts were experimentally removed from five clonal genotypes of the grain aphid, Sitobion avenae Fab., which were then exposed to frost. 3. Aphid genotypes differed considerably in survival following the exposure and in fecundity of the survivors. However, the presence of the facultative symbionts had no overall effect on the studied traits. 4. The results suggest that the facultative symbionts have limited effects on the cold hardiness of their grain aphid hosts. © 2011 The Authors. Ecological Entomology © 2011 The Royal Entomological Society.